COMPARATIVE ANALYSIS OF INFINITIVE SECONDARY PREDICATES IN ENGLISH AND UZBEK LANGUAGES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In this article, the main features of the English and Uzbek verbs were analyzed. The main differences between Uzbek and English verbs were shown.